IMPLEMENTING E-COURSES IN FOREIGN LANGUAGE TRAINING - HASKOVA, Alena; Eva, MALA; TURCINOVA, Karina (Trends in education, 2014)
Information and communication technologies used by foreign language teachers at higher education institutions influence the effectiveness of the teaching/learning process. The authors in their paper present a comparison of the results of two projects aimed at implementing e-courses in English language training. They emphasize the introduction of innovative elements, such as discussion forum, hyperlinks, video-sequences, or creating a glossary of terms by learners themselves. All of them help increase students extasciiacute motivation and improve their attitude to online education.
Keywords: improving the quality of e-courses; English language teacher training; foreign language competencies of other teachers.